(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The implementation of ubiquitous learning continues to be being developed, along side the issues that regularly rise up from the software of digital and online larning, consisting of alienating college students from the actual world, the problem of college students specializing in studying goals, giving college students possibilities to spend their studying time with entertainment, to the hassle of growing the cognitive load of college students. As a continuation of electronic learning and mobile learning, ubiquitous learning gives extra than simply the cutting-edge academic thoughts or methods. To find out some considerations in designing a ubiquitous learning environment, the method used is a literature review. The literature review process begins with determining the concepts to be developed, identification and tracing of previous research results, mapping and classification of research results, analysis of classification and theme determination, analysis of relationships between themes, and conclusions. Based on the literature review process, several themes were found in the discussion, namely: 1) the emergence concept of ubiquitous learning, 2) learning theory that underlies ubiquitous learning, 3) characteristics of ubiquitous earning environment, 4) prinsiples of ubiquitous earning environment, 5) mobile devices as tools in ubiquitous earning, 6) moodle learning management system, 7) program mapping, and 8) criteria for ubiquitous learning system quality.